2009
DOI: 10.4319/lo.2009.54.4.1098
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity and morphology in deep ultraoligotrophic Andean lakes: The role of UVR on vertical distribution

Abstract: We investigated the community composition and the relative size-shape distribution of bacterial assemblages in deep transparent lakes, where bacteria may be affected by harmful ultraviolet radiation (UVR). Summer samples of the euphotic zones of nine ultraoligotrophic lakes located in different drainage basins between 40u279 and 42u499S in the North Andean Patagonia were analyzed for relative diversity by denaturating gradient gel electrophoresis and the bacterial morphology (free-living cocci and rods vs. fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…This probe-defined cluster was found to be present in 98 of 102 diverse freshwater habitats in Europe that were surveyed for their presence, in abundances of up to 29% of the total number of DAPI-stained bacteria (190). This clade has also been detected by its 16S rRNA gene sequences in nearly every lake studied by using this technique, including Lake Gossenkollesee in Austria (63), Lake Grosse Fuchskuhle in Germany (63), Lake Baikal in Russia (63), deep Patagonian lakes (35), Tibetan lakes (127), eutrophic Swedish lakes (48), shallow eutrophic lakes in Belgium (214), shallow eutrophic Lake Taihu in China (233), oligotrophic Crater Lake in Oregon (212), oligotrophic Toolik Lake in Alaska (38), and a variety of lakes in Wisconsin (this study). The cluster seems to be more abundant under circumneutral to alkaline pH conditions than in acidic or humic habitats and most abundant in small shallow ponds (190).…”
Section: Class Betaproteobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…This probe-defined cluster was found to be present in 98 of 102 diverse freshwater habitats in Europe that were surveyed for their presence, in abundances of up to 29% of the total number of DAPI-stained bacteria (190). This clade has also been detected by its 16S rRNA gene sequences in nearly every lake studied by using this technique, including Lake Gossenkollesee in Austria (63), Lake Grosse Fuchskuhle in Germany (63), Lake Baikal in Russia (63), deep Patagonian lakes (35), Tibetan lakes (127), eutrophic Swedish lakes (48), shallow eutrophic lakes in Belgium (214), shallow eutrophic Lake Taihu in China (233), oligotrophic Crater Lake in Oregon (212), oligotrophic Toolik Lake in Alaska (38), and a variety of lakes in Wisconsin (this study). The cluster seems to be more abundant under circumneutral to alkaline pH conditions than in acidic or humic habitats and most abundant in small shallow ponds (190).…”
Section: Class Betaproteobacteriamentioning
confidence: 99%
“…Likewise, the dominance of the Actinobacteria is spread across the globe. Studies have shown high actinobacterial abundances in lakes in North America (140), Europe (63), Africa (44,45,101), Asia (82,142,230), Australia (84), South America (35), and Antarctica (149,150).…”
Section: Phylum Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the effects on picoplankton of the underwater photosynthetically active radiation (PAR) and of ultraviolet (UV) radiation has therefore received much attention. This research has highlighted the changes in the activity and in the morphology of the autotrophic and heterotrophic picoplankton with increasing intensity of the UV radiation and with modification of the spectral composition of the underwater PAR (Callieri et al, 1996;Vörös et al, 1998;Bertoni and Callieri, 1999;Modenutti et al, 2005;Corno et al, 2009;Callieri et al, 2011). Our ability to analyze the microbial world received a considerable boost from molecular biology, and particularly from DNA amplification and analysis techniques.…”
Section: The Aquatic Microbial Ecology Of Freshwatersmentioning
confidence: 99%
“…Molecular ecological techniques have recently been used to study in situ questions of prokaryotic (bacterial and archaeal) diversity (Callieri et al, 2009), using CARD FISH (Catalyzed Reporter Deposition Fluorescence In Situ Hybridization) techniques with specific fluorescent probes and subsequent epifluorescence microscopy examination. The relevance of this approach lies in the fact that many aquatic microorganisms cannot be easily cultured in the laboratory, which would allow for their identification and characterisation with classic microbiological methods.…”
Section: Molecular Ecologymentioning
confidence: 99%